Effects of lycopene on the model of oleic acid-induced acute lung injury - Turkoglu, Suat; Muz, Mehmet Hamdi; Ozercan, Resat; Gursu, Ferit; Kirkil, Gamze (Turkish Assoc Tuberculosis & Thorax, 2012)
Introduction: This study, we aimed to investigate the protective effect of lycopene in lung injury rat model. Materials and Methods: Twenty eight Wistar rats were enrolled into the study. Control group (n=7) were applied PBS + ethanol (9/1). A single dose of 100 mg/kg oleic acid (OA) intravenously was administrated to OA group (n=7). One mL of corn oil was given daily to corn oil + OA group (n=7) by gavage for five weeks. Lycopene was given by gavage to lycopene + OA group (n=7) for five weeks. At the end of the 5th weeks, OA were given. Four hour after OA administration, lung tissue, blood samples were taken. Malondialdehyde, superoxide dismutase, glutathione-peroxidase, catalase levels were determined. Results: Malondialdehyde levels of serum, lung tissues were increased in OA, corn oil + OA groups than control, where as decreased to controls levels in lycopene + OA group (p< 0.05). Superoxide dismutase, glutathione-peroxidase activities of serum, tissue increased moderetaly or they were closed with control values. There was significant increase in lycopene + OA group values. Histopathological examination of control group was normal. OA, cornoil + OA groups had perivascular, alveolar edema, hemorrage, prominent neutrophil infiltration, destruction in alveolar structure. Lycopene + OA group had less neutrophilic infiltration, perivascular, alveolar edema. Conclusion: Lycopene rich diet may have an important role preventing damages in lungs.
Oleik asit ile oluşturulan akut akci?er hasarı modelinde likopenin etkileri
Keywords: Acute lung injury; rat model; lycopene; oxidant; antioxidant